A Comparative Study between Intravenous Lidocaine (0.5%) and Prilocaine (0.5%) in Intravenous Regional Anesthesia (Bier’s Block) - Saber, Hiwa Fateh; Mahboba, Jaafar Hameed Jaafar; AbdulHamid, Sardasht (AL-Kindy College Medical Journal, 2025)
Background: Bier’s block is a reliable, straightforward, and safe technique for anesthetizing upper limb. This study aimed to compare between the effectivity of IV Lidocaine (0.5%) and IV Prilocaine (0.5%) in Bier’s block in terms of onset and recovery time of sensory and motor block, tourniquet tolerance, vital signs during and after surgery, and the need for intraoperative analgesia.Subjects and Methods: This study was conducted at Erbil Teaching Hospital and Emergency Hospital, from the period of May 2021 to October 2021. In this prospective, randomized, double-blind study, two groups of 25 patients were prepared for hand operation. Patients in group A were given IV Lidocaine (0.5%) while patients in group B were given IV Prilocaine (0.5%). Sensory and motor block and their recovery times, tourniquet pain, intra-operative analgesic needs, vital signs, and visual analog scale (VAS) scores were recorded.Results: No significant difference was found in the onset of sensory and motor block in both Lidocaine (5.5±1.6 min) and Prilocaine (5.9±1.6 min) groups (p-value=0.319), while the recovery of sensory block after releasing tourniquet was significantly shorter in Prilocaine group (7.4±1.4 min vs. 5.4±0.8 min) (p-value=0.003). The VAS score of Prilocaine group during and after surgery was significantly higher, with more patients receiving analgesia (5 vs. 2).Conclusions: Both IV Lidocaine (0.5%) and IV Prilocaine (0.5%) appeared to be effective local anesthetics in Bier’s block of distal upper extremity, intraoperatively and postoperatively. IV Lidocaine (0.5%) provided greater analgesia, while IV Prilocaine (0.5%) exhibited quicker sensory block recovery after tourniquet cuff release.